2014
DOI: 10.3389/fmicb.2014.00377
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Aspergillus section Flavi in Europe in relation to the management of aflatoxin risk

Abstract: Aflatoxins and the producing fungi Aspergillus section Flavi are widely known as the most serious and dangerous mycotoxin issue in agricultural products. In Europe, before the outbreak of aflatoxins on maize (2003–2004) due to new climatic conditions, their contamination was confined to imported foods. Little information is available on molecular biodiversity and population structure of Aspergillus section Flavi in Europe. Preliminary reports evidenced the massive presence of Aspergillus flavus L -morphotype a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 56 publications
1
49
0
1
Order By: Relevance
“…In general, AFM 1 levels in dairy milk in Europe are low: only around 0.06% of about 12000 samples were above the EU limit of 0.05 μg/kg milk (EFSA ). However, when incidents occur, this may lead to widespread AFM 1 contamination in milk as was the case in Italy in 2003 (Perrone and others ). It is expected that the tight restrictions on controlling AFB 1 in feed intended for dairy cattle may not be applied in the same way for feedstuffs intended for other animals, such as goats and sheep.…”
Section: Resultsmentioning
confidence: 99%
“…In general, AFM 1 levels in dairy milk in Europe are low: only around 0.06% of about 12000 samples were above the EU limit of 0.05 μg/kg milk (EFSA ). However, when incidents occur, this may lead to widespread AFM 1 contamination in milk as was the case in Italy in 2003 (Perrone and others ). It is expected that the tight restrictions on controlling AFB 1 in feed intended for dairy cattle may not be applied in the same way for feedstuffs intended for other animals, such as goats and sheep.…”
Section: Resultsmentioning
confidence: 99%
“…Worryingly, surveys demonstrated that higher levels of aflatoxins in agricultural commodities were linked to upraising climatic conditions (Streit et al, 2013). Indeed, AFB1's contamination was recently reported on crops from other temperate regions of Europe, demonstrating an increased distribution of this mycotoxin potentially related to global climate changes (Battilani et al, 2016;Perrone et al, 2014). Even if several approaches have been developed to limit AFB1's contamination (Wild et al 2015;Jalili, 2015), they remain insufficient to completely avoid mycotoxin contamination thus emphasizing the need to develop new strategies to guarantee food safety.…”
Section: Introductionmentioning
confidence: 99%
“…Aflatoxin, a fungal secondary metabolite is mainly produced by toxigenic strains of Aspergillus species, especially A. flavus and A. parasiticus (Klich, Tang, & Denning, 2009). In addition, A. flavi has also been reported as the prime fungal colonizers of peanut seeds (Perrone, Gallo, & Logrieco, 2014;Sultan & Magan, 2010). In general, moderate temperature (27-38 C) and high humidity are inductive for the growth of Aspergillus and can lead to aflatoxin contamination at both pre and postharvest levels (Fernández-Cruz, Mansilla, & Tadeo, 2010;Kimatu, McConchie, Xie, & Nguluu, 2012).…”
Section: Introductionmentioning
confidence: 99%